PENYUSUNAN SISTEM ANGGARAN BERBASIS KINERJA pada KABUPATEN PANDEGLANG, PROVINSI BANTEN - Subarkah, Pujiatmo (Jurnal Desentralisasi, 2012)
This study reviews the concept of performance- based budgeting and how it has been applied. The research method used for this research isqualitativemethod which givesan analytic meaning by studying and collecting data based on relevance theory. This study shows that Performance- based budgeting has achieve significant. It can be said that most of the implementation has refer to the theory. Finally, the local governance of Pandeglang, Banten Provinces made strong efforts to improve the implementation although in the practice still constrained technical issues.